Efficacy Of Hypermedia-Based Reading On Communicational English; An Experimental Study Based On ‘Daily News’ E-Paper - Mohideen Bawa Nowzath; Singanayagam Umashankar; Mohamed Jabeer Fathima Sujani (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
The implication of hypermedia-based learning with electronic newspaper; denotes to enable the knowledge with graphics, images, animation, sound and hypertext displays a chief role in the action of the students. This research was led to discover the connection between the hypermedia-based newspaper reading under the speaking subject in the Higher National Diploma in Accountancy syllabus with learning strategies: responsibilities and actions in newspaper place with picture method and the performance in the communicational English in HNDA course of Sri Lanka Institute of Advanced Technological Education as there were no any previous research studies done in the academic field. Ninety students from HNDA – A were engaged as an experimental group and ninety students from HNDA- B were occupied as a controlled group. A pre-test was accompanied for the groups to find the earlier knowledge of the students in the communicational English proficiency and the mean differences were found to be negligible for the groups. Later, the experimental group was used to pursue hypermedia-based newspaper (Sri Lanka Daily News) reading on the strategies; responsibilities and actions in newspaper place with picture method for six months with sixty hours learning while the controlled group was trained without the use of hypermedia-based newspaper reading. After six months a post-test was conducted for the groups. When it was conducted the mean was somewhat improved for the group - B, and the mean was noticeably developed for the group - A. Therefore, the research findings denote that hyper-media newspaper reading improves communicational English of the learners.